2011
DOI: 10.1002/app.35422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new compatibilisant agent PVC‐g‐MA and its use in the PVC/alfa composites

Abstract: ABSTRACT:The main objective of this research was to synthesize a new compatibilisant agent (PVC-g-MA), which was grafted from the maleic anhydride on the PVC chains. The presence of maleic anhydride grafting on PVC was made evident by infrared analysis. PVC-g-MA was used like compatibilisant to solve the problem of the incompatibility between the hydrophobic polymeric matrix (PVC) and hydrophilic fiber (alfa). Composites samples were prepared with different alfa fiber loading (10, 20, and 30 wt %) and incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Sreenivasan et al reported that the permanganate treatment on sansevieria cylindrica fibers increased the percentage of crystallinity index. Hammiche et al studied the effect of poly(viny lchloride)‐grafted‐maleic anhydride PVC‐g‐MA (1, 3, and 5%) on PVC/alfa fiber. They have found that the tensile strength of the composites with PVC‐g‐MA was higher than that of the untreated composites.…”
Section: Introductionmentioning
confidence: 99%
“…Sreenivasan et al reported that the permanganate treatment on sansevieria cylindrica fibers increased the percentage of crystallinity index. Hammiche et al studied the effect of poly(viny lchloride)‐grafted‐maleic anhydride PVC‐g‐MA (1, 3, and 5%) on PVC/alfa fiber. They have found that the tensile strength of the composites with PVC‐g‐MA was higher than that of the untreated composites.…”
Section: Introductionmentioning
confidence: 99%
“…18 Hydrophilic character of natural fibers leads to poor resistance to moisture and low interfacial properties between fiber and polymer matrix, which reduces their potential as reinforcing agents.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…physical or chemical) and others were based on the addition of a coupling agent (or compatibilizer) for interfacial adhesion improvement. 14 For fibre modification, researchers studied types of chemical treatment of natural fibre, in order to improve the compatibility between both components. Chemicals may activate hydroxyl groups or introduce new moieties that can effectively interlock with the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Hemi-cellulose is strongly bound to cellulose fibrils presumably by hydrogen bonds. 1,[13][14][15][16][17][18] The abundance of hydroxyl groups in natural fibre makes it incompatible with the hydrocarbon plastic material. Furthermore, the presence of impurities in the outer layer of natural fibre makes it more difficult to interact with the hydrocarbon plastic material.…”
Section: Introductionmentioning
confidence: 99%